Digitalisasi Sebagai Upaya Pengembangan Sumber Daya Aparatur Pemerintah Desa Di Desa Sugihwaras - Lilik Maslikhah (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2023)
Digitalization in village governance is a growing phenomenon in Indonesia in recent years. The purpose of this digitization is to increase the efficiency and effectiveness of public administration and reduce bureaucratic problems. This paper focuses on digitization in Sugihwaras Village and tries to explain the challenges faced by rural areas and present possible solutions to overcome these challenges. This study uses a qualitative-descriptive method with a library research approach. Data was collected through searching academic literature, books, journals and articles from relevant online and offline sources. In this research, digitization in Sugihwaras Village is analyzed in the context of developing village government apparatus resources. The results of the study show that Sugihwaras Village has implemented digitalization through the SiPraja 4.0 program. This program has provided improved public services with higher efficiency in obtaining permits. Adequate communication infrastructure and expertise in digitalization in Sugihwaras Village also contribute to the successful implementation of digitalization. However, there are still challenges to digitalization in rural areas, such as limited infrastructure, low digital literacy, and inadequate funding. To overcome this challenge, the government and private sector organizations need to work together to ensure that the benefits of digitalization are accessible to all villagers, especially those in remote and underdeveloped areas. With increased digitization in Sugihwaras Village and the successful experience achieved, this research contributes to optimizing the use of digital technology in village administration and formulating appropriate policy recommendations for developing village government apparatus resources.